MEDICINAL BIOMAGNETISM FOR ANALGESIA IN MUSCULOSKELETAL DISORDERS OF THE SPINE – APPLICATION OF STATIC MAGNETIC FIELDS USING THE SPINE PROTOCOL - José Pereira, Rui; Porto Bitencourt, Noeli; Puppi Bastos Mellem, Larissa; dos Remédios da Silva, Maria; Viapiana Bossa, Adriane; Blanche Mathieu Graf, Livia; Mara Rambo Martini, Angela (Health and Society, 2023)
Introduction: Spinal pain affects approximately 80% of the population at some point of their lives. It’s the second biggest cause of absenteeism in professional or academic environments, directly impinging upon reduced productivity, psychological states and quality of life. Allopathy is the most widely used treatment, however its adverse effects are recurrent. Medicinal Biomagnetism (MB) is a therapy that uses static magnetic fields (SMF) provided from magnets, which have minimal side effects, assisting in the restoration of health, yielding an analgesic effect. Goal: Evaluate the effect of SMF usage by means of the Spine Protocol (SP) from MB applied onto pain deriving from musculoskeletal disorders of the vertebral column. Methodology: Longitudinal study with clinical trials of 15 participants assessed using the Visual Analogue Scale (VAS) and Brief Pain Inventory, followed up after treatment for 30 days. Result: A reduction in pain perception was observed in 91% of the sample, representing 21 treatments of spinal segments, from just 15 minutes of exposure to the SP procedure, with a significative difference for the VAS variables (p=0.0000014). Most participants were female and the most common pain was located around the lumbar segment region. Conclusion: The SP procedure has therapeutic potential in both short and long term for the treatment of acute and chronic pain of any intensity, and it can be considered as a primary or supporting intervention in musculoskeletal disorders of the spine. It has demonstrated a shorter initial time and a longer duration for its analgesic effect when compared with the drug action reported in the literature.